Zeolite supported mono- and bimetallic oxides: Promising adsorbents for removal of As(V) in aqueous solutions - Simsek, Esra Bilgin; Ozdemir, Ercan; Beker, Ulker (ELSEVIER SCIENCE SA, 2013)
In this study, synthesis and characterization of novel adsorbents based on natural zeolite (clinoptilolite) supported mono- (Fe or Al) and bimetallic (Fe-Al) oxides for adsorption of arsenate from aqueous solution were investigated. Batch sorption experiments were carried out at different pH (3.0, 5.0 and 7.0), temperature (298, 318 and 338 K) and initial metal concentration (0.5, 5.0 and 9.5 mg L-1) values. The experimental results showed that aluminum (ZNa-Al) and iron (ZNa-Fe(II)) modified zeolites enhanced the arsenate uptake significantly. Furthermore, bimetallic oxide associated zeolite, ZNa-AlFe(III), showed highest adsorption capacity as compared to ZNa-Al and ZNa-Fe(II), indicating that aluminum impregnation can provide more adsorption sites (Al OH) to As(V) anions. Maximum sorption capacities were achieved at pH 5 for ZNa (0.026 mg g(-1)), ZNa-Al (1.50 mg g(-1)) and ZNa-AlFe(III) (3.86 mg g(-1)) and at pH 3 for ZNa-Fe(II) (3.02 mg g(-1)). The results suggest that As(V) adsorption process is dominantly followed by surface complexation reactions for ZNa-Al and ZNa-AlFe(III) adsorbents while columbic interactions occur on the surface of ZNa-Fe(II). Dubinin-Radushkevich and Freundlich isotherm models fitted the equilibrium data better than Langmuir isotherm. The Gibbs free energy values were found as negative for all sorbents, which indicates the adsorption of arsenate on modified zeolites is feasible and spontaneous. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Arsenic; Batch adsorption; Natural zeolite; Mono- and bimetallic oxides; ARSENIC ADSORPTION; IRON; CLINOPTILOLITE; WATER; SORPTION; AS(III); EQUILIBRIUM; BIOSORPTION; DESORPTION; MANGANESE; Engineering